2011
DOI: 10.1557/opl.2011.400
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-based Materials as Key-enabler for “More Than Moore”

Abstract: Carbon-based materials like nanotubes and graphene are heavily investigated as future CMOS-like devices and in interconnect applications. While much of the interest has been devoted to the device aspects in competition to conventional CMOS transistors, the paper here will focus on some less known applications of carbon. Proposed and demonstrated are interconnect applications like highly conductive electrodes for capacitors, gate material or through-silicon vias (TSV), novel non-volatile memories, carbon-silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Carbonaceous materials offer tunable electrical properties, thermal and chemical stability, and flexibility so are increasingly used in electronics . We have shown that by depositing C from an energetic plasma, highly rectifying graphitic (semimetallic) contacts can be made on p‐type Si and n‐type 6H‐SiC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonaceous materials offer tunable electrical properties, thermal and chemical stability, and flexibility so are increasingly used in electronics . We have shown that by depositing C from an energetic plasma, highly rectifying graphitic (semimetallic) contacts can be made on p‐type Si and n‐type 6H‐SiC .…”
Section: Introductionmentioning
confidence: 99%
“…Carbonaceous materials offer tunable electrical properties, thermal and chemical stability, and flexibility so are increasingly used in electronics. 1,2 We have shown that by depositing C from an energetic plasma, highly rectifying graphitic (semimetallic) contacts can be made on p-type Si 3 and n-type 6H-SiC. 4 These contacts are formed at sufficiently low temperatures to be compatible with photolithography, enabling accurate control of device dimensions/ locations.…”
Section: Introductionmentioning
confidence: 99%
“…Over the recent years, graphene has been investigated for applications in microelectronic. And due to their low specific resistivity, graphene is used for applications in interconnects as well [1]. Several graphene layers which stacked with each other are called Graphite and used in many Carbon Composites.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that graphenic carbon (GC) is a suitable window material as it is deposited directly from a gas phase onto a silicon substrate and overcomes the inadequate adhesion by forming strong silicon carbon bonds . The inherently high bonding of the GC window material to a silicon frame not only hinders delamination but also acts as a gas tight barrier in contrast to graphene that adheres by van der Waals forces .…”
Section: Introductionmentioning
confidence: 99%